Biodistribution studies of two 18F-labeled pyridinylphenyl amides as subtype selective radioligands for the dopamine D3 receptor - Hocke, Carsten; Cumming, Paul; Maschauer, Simone; Kuwert, Torsten; Gmeiner, Peter; Prante, Olaf (Nuclear Medicine and Biology, 2014)
Introduction: Dopamine D3 receptors are implicated in various neuropsychiatric diseases, drug abuse and alcoholism, but specific agents for D3 molecular imaging are lacking. We evaluated two in vitro selective fluorine-18-labeled radioligand candidates ([F]5 and [F]6) for positron emission tomography (PET) imaging of D3 receptor availability in the brain. Methods: Biodistribution was evaluated in Sprague-Dawley rats using ex vivo autoradiography and small-animal PET. Protein binding studies were conducted in human plasma and cerebrospinal fluid. Results: [F]5 showed rapid blood-brain barrier penetration and fast washout after intravenous injection, whereas the rat brain penetration of [F]6 was lower. The total distribution volume (V) of [F]5 was 20-26mL g throughout brain. Co-injection with the D3 antagonist BP897 resulted in globally increased cerebral washout of [F]5 and [F]6, but SUV analysis and parametric mapping of binding potential (BP) relative to the cerebellum did not reveal specific binding of either ligand in D3-rich brain regions, i.e. the ventral striatum. However, there was substantial displaceable binding of [F]5, and to a lesser extent [F]6, in the pituitary. Conclusion: These radioligands reveal dopamine D3 receptors in the pituitary, but are not suitable for PET imaging of in brain, possibly due to low specific signal relative to the globally high V. © 2014 Elsevier Inc.